Epidemiological Characteristics of COVID-19 Resurgence in Areas Initially Under Control - Li, Yazhen; Yang, Kai; Zha, Shanshan; Wang, Lingwei; Chen, Rongchang (Frontiers in Public Health, 2021)
Objectives: To investigate the epidemiological characteristics and infection routes of new cases in order to provide information for preventing COVID-19 resurgence in areas initially under control. Methods: The information of new symptomatic and asymptomatic patients in Chinese mainland was collected. The location distribution, epidemic course, infection routes and patients’ characteristics of outbreaks were described and analyzed. Results: There were 43 new outbreaks with 3795 symptomatic patients in Chinese mainland from March 21, 2020 to June 13, 2021. These outbreaks mainly occurred in central, border and coastal port cities. The main infection route of first generation indigenous patients was contact with imported cases and contaminated goods or environments. The infection routes of secondary generation patients mainly included family transmission, indoor social gathering infection, nosocomial infection and other infection routes. Family transmission was the most common infection route, and indoor social gathering was the most important reason for the large-scale outbreaks. Conclusions: Strengthen the management of imported patients and staff in high-risk posts was the key point to avoid the first generation indigenous patients. Adequate family isolation, prompt management policies for indoor public place and monitor of population at risk of infection were key strategies for preventing COVID-19 resurgence in areas initially under control.